Review on Wearable Antennas and their Applications - Christina, G. (IRO Journal on Sustainable Wireless Systems, 2022)
Wearable antennas are one of the primary sources for the Body Area Networks (BAN). It allows the users to sense, communicate, transfer and exchange data to a remote server with the help of IoT gateway. The size, speed, and power consumption play a major role in the design of wearable antennas. In most of the applications, the wearable antennas are connected over the cloth of the user and in rare cases the antenna is fixed over or under the skin of the user. The motive of this paper is to review the technologies behind the design of wearable antennas and their applications in various fields. Moreover, the paper determines the research gap in the field of wearable antenna designing.